Evaluation of Public Prosecution Records of Women Exposed Domestic Violence in Trabzon - Yarış, Füsun; Savran, Bülent; Birincioğlu, İsmail and Kartı, Deniz (The Bulletin of Legal Medicine, 2002)
To evaluate the sociodemographic data of the women exposed to domestic violence in Trabzon was aimed in the study. Public prosecution records of the 164 domestic violence cases who live in Trabzon and had been decided not to prosecute, from the 363 women reported by Department of Council of Forensic Medicine were investigated. Mean age was 30.9 (10-67) years. Sixty-four% of the cases (n=105) were married. One- hundred-twelve (68.3%) cases had children, 6 cases (3.7%) were illiterate, 58.5% (n=96) were graduated of primary school. Onehundred-two (62.2%) cases were housewives. Eighty-ni-ne% (n=146) were exposed to physical and verbal, 9.8% (n= 16) verbal, 1.2% (n=2) sexual, physical and verbal violence. The violence was continuous in 31.7% (n=52) cases. 65.2% (n= 107) were beaten at home. Assailants were the husbands in 68 (41.5%) cases. As majority of the cases were exposed to physical and verbal violence at home, graduated of primary school and had children; women in low social status were seen to be affected more. Key Words: Domestic violence, woman.